REPRESENTASI MAKNA PESAN MORAL DALAM LIRIK LAGU “ESOK KAN BAHAGIA” KARYA D’MASIV - Dery Wandi AL; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In a work of music there are elements that are important in addition to musical arrangements. One of the most important things in a music is the existence of the lyrics of the song. Through song lyrics written by listeners songwriters are invited to interpret through the brain that stores experience and knowledge an process it as a basic foundation in digesting the beauty of the song lyrics. This study aims to express the meaning of denotation, connotation, an the myth of moral messages contained in the lyrics of Esok Kan Bahagia.Research method used is semiotics analysis of Roland Barthes. Research uses a qualitative-interpretative from of research. The subject of this research is the lyrics of Esok Kan Bahagia. The object of research is the meaning of denotation, connotation, and myths in the lyrics of Esok Kan Bahagia. In data collecting researcher using documentation technique, an literature study.The result of the research slow that the lyrics of Esok Kan Bahagia tune present the meaning of the moral message that is seen directly from the meaning of denotation, connotation, and myth in every lyrics of the song. Moral message in the lyrics of Esok Kan Bahagia song that is moral message of human relationship with god in the form of sincerity and always grateful to him. Human moral message with humans in the form of an invitation to fight and spirit. Human moral message with human person in the form of optimistic and more patient.